Extended-release divalproex in bipolar and other psychiatric disorders: A comprehensive review - Steven C Stoner (Dove Medical Press, 2007)
Steven C Stoner1, Megan M Dahmen21Northwest Missouri Psychiatric Rehabilitation Center, Department of Pharmacy, St. Joseph, Missouri, USA; 2University of Missouri-Kansas City School of Pharmacy, Division of Pharmacy Practice, Kansas City, Missouri, USAAbstract: Bipolar disorder can be a devastating disease state for individuals with the disease and also for family members. Proper recognition and treatment is vital to the successful management of this disease state. Through increased community and practitioner awareness, along with efforts to increase awareness for proper assessment, the rate of diagnosed bipolar disorder is increasing. Recent years have brought about the introduction of several new medications with approved indications for the treatment of bipolar disorder. In addition to new agents, traditional mood stabilizing medications have also been released in different formulations to better enhance tolerability without jeopardizing efficacy. One particular product is extended-release divalproex sodium. In the following article, we review the clinical presentation of bipolar disorder, its epidemiology, and the pharmacokinetics and mechanism of action for divalproex. In addition, we specifically review the role of extended-release divalproex in bipolar disorder through a critical analysis of the currently available published primary literature.Keywords: extended-release divalproex, divalproex, bipolar disorder, mania, depression